An approach for multi-agent coordination based on semantic approximation. (15th May 2009) - Ma, Yinglong; Zhang, Shipeng; Li, Yuancheng; Yi, Zheng; , Shaohua Liu
Ontology plays an important role in multi-agent systems because it can provide and define a sharable semantic vocabulary. However, it is almost impossible for distributed web agents to completely share a same semantic vocabulary. Information incompleteness and semantic heterogeneity among distributed ontologies will make multi-agent communication rather difficult. In this paper, we exploit semantic approximation technologies for implementing better multi-agent communication based on partial shared distributed ontologies. Through approximate semantic coordination among multiple agents, we can further obtain effective semantic query results and achieve information sharing across distributed ontologies. We also developed a multi-agent system called OntoQ which is based on semantic approximation and coordination for illustrating our approach.